PRODUKSI BIOGAS DARI MAKROALGA MERAH (Gracilaria verrucossa) PADA SISTEM BATCH - Dea Fauzia Lestari; Mujizat Kawaroe; Salundik Salundik (Fakultas Perikanan dan Ilmu Kelautan, 2015)
Marine macroalgae become one of biomass resource to be converted into energy using anaerobic degradation. This process requires bacteria agent contained in cattle rumen or manure. Availability of residual Gracilaria verrucosa (rejected) on fishpond macroalgae cultivation support for biogas energy development. The aims of this research were analyzing biogas production from red macroalgae Gracilaria verrucosa and applying the gas to biogas lamp and stove. The method in this research was batch system, used 1500 L capacity digester with 1200 L working volume. Methane production average volume was 72 L/day during 31 days of observation. The trials were carried out to operate lamp and stove, biogas lamp require 1.80 L/min and biogas stoves require 6.00 L/min gas from digester. This research may be applied and developed when supported by availability of macroalgae biomass as the prime substrate.